Protomauroania mikhailovi—a new species of malachite beetles (Coleoptera, Dasytidae) in Rovno amber - Tshernyshev, Sergei E.; Perkovsky, Evgeny E. (Zootaxa, 2021)
A new species of malachite beetles, Protomauroania mikhailovi Tshernyshev & Perkovsky, sp. n. is described from late Eocene Rovno amber. The new beetle is the second species of the Eocene fossil genus Protomauroania Tshernyshev, 2021 that was first recorded in Rovno amber and shows fauna similarity of dasytids in Baltic and Rovno amber. The new species is typical owing to the following characters: antennae with 5-segmented wide club, surface covered with dark-brown long semi-erect thin setae, and the ultimate ventrite (apical sternite) simple, narrow, not depressed. Digital high resolution pictures of the beetle are provided.